IMPLEMENTASI UNDANG-UNDANG NOMOR 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK TERHADAP KEKERASAN DALAM KELUARGA DI KECAMATAN BAE, KUDUS - Ngazizah, Inna Fauziatal (JIL : Journal of Indonesian Law, 2025)
This study aims to analyze the effectiveness of the implementation of Law Number 23 of 2002 on Child Protection in safeguarding children from violence within the family environment in Bae Subdistrict, Kudus Regency. This research employs a qualitative legal approach, with data collected through structured interviews with three informants from Bae Subdistrict. The findings indicate that the implementation of the law has not been fully effective in protecting children’s rights, as evidenced by the persistently high cases of violence against children, economic exploitation, and inadequate fulfillment of children’s social and health rights. Factors affecting the effectiveness of the law include low public awareness, limited government involvement, and the socio-economic conditions of families. The recommendations proposed involve enhancing legal dissemination, strengthening the role of child protection institutions, and optimizing child protection policies to ensure the comprehensive fulfillment of children’s rights.